(untitled) (International Journal of Language, Literacy and Translation, 2025)
Tourism in Thailand is one of the powerful and dynamic industries which drives the economy of the country. Offering a variety of natural attractions, food and culture, Thailand becomes a renowned destination among tourists from all over the world. Tourism Authority of Thailand (TAT) is the official organization playing a significant role in supporting and promoting tourism business. Apart from websites, guidebooks and other promotional materials, Amazing Thailand promotional videos have been created and uploaded on YouTube by TAT to promote Thai culture to foreign tourists. Thai and English subtitles are added to the videos to narrate travelling experiences in Thailand. The purpose of this qualitative research is to explore the cultural categories and translation procedures of culture-specific items from English subtitles of Amazing Thailand promotional videos according to Newmark cultural translation framework (1988). The data of 110 culture-specific items were collected from 64 Amazing Thailand promotional videos by purposive sampling. The result showed that the most common category of culture-specific items is material culture (artefacts) while couplets is the most frequently used translation procedure in Amazing Thailand promotional videos. The finding from this study could shed light on translation of culture-specific items. It also encourages translators and tourism officers to get some ideas about translating tourism promotional content of their own particular culture and context.